A Simple Method for Enema Administration in One-Day-Old Broiler Chicks - Marietto-Goncalves, Guilherme Augusto [UNESP]; Grandi, Fabrizio [UNESP]; Andreatti Filho, Raphael Lucio [UNESP] (Hindawi Publishing Corporation, 2012)
The present study aimed to describe a simple technique for enema administration in one-day-old broiler chicks. For this purpose we used 455 unsexed health birds divided into four groups submitted to three different experimental protocols: in the first one, we measured the total length of the large intestine in order to establish a secure distance for probe introduction; in the second, we evaluated maximum compliance of large intestine and diffusion range; finally, based on results obtained we tested the hypothesis in 400 birds in order to standardize the method. Enema solutions applied in an intrarectal manner with a stainless steel gavage BD-10 probe into one-day-old broiler chicks at 0.2 mL at a distance of 1.5 cm proved to be a reliable method.